Hotels and Airbnb Accommodations in the Greater Yogyakarta Urban Region - Indonesia: Competition or Complementarity? - Azis Musthofa; R. Rijanta (Jurnal Perkotaan, 2025)
Tourism, as the backbone of the economy of Yogyakarta Municipality, is also the main source of demand for accommodation services. Under these circumstances, Airbnb penetrates the accommodation market in the Greater Yogyakarta Urban Region (GYUR). As a company using the principle of the sharing economy, it specialises in accommodation services. Airbnb has grown tremendously, as it acquired 1,164 accommodation partners in the GYUR in 2017. The hotel industry is probably among the most affected by the presence of Airbnb. The rise of the sharing economy platforms seems to create competition between hotels and Airbnb accommodations. This paper focuses on examining the competition between hotels and Airbnb accommodations in the GYUR both in spatial and temporal terms. This research was conducted based on secondary data analysis and field observations. Secondary data analysis was performed through mapping of the distribution of hotels and Airbnb accommodations to explore possible competition between the two. Field observations focus on describing the neighbourhood environments and the accessibility of both types of accommodations. The research shows that Airbnb accommodations are mainly concentrated in the densely populated areas in the urban centre and in tourism-associated areas. Hotels are located in the best part of the city and are situated in close proximity to the city centres, allied infrastructure, and facilities. The high demand for accommodation in the GYUR enables the locals to register their assets as Airbnb accommodation. This is also caused by the absence of regulations governing this home-sharing activity.